Nature of Work of Accountants: The Case of Accounting Service Firms in Hanoi, Vietnam - Nguyen Van Thu; Nguyen Van Tri (International Journal of Small and Medium Enterprises and Business Sustainability, 2021)
In accounting service firms in Hanoi, nature of work of accountants is consistent with the accountants, but not fully. The main objective of this study was to identify, evaluate, and to measure the attributes of nature of work of accountants in accounting service firms in Hanoi, Vietnam. The study was based on a field survey using a semi-structured questionnaire on a sample of 150 accountants. But only 120 filled questionnaires were satisfactory and therefore included in the analysis. By using seceral statistical analytical tools, i.e. descriptive statistics, Cronbach’s Alpha analysis, Independent t-test and ANOVA, the study has identified and measured five (5) attributes of nature of work of accountants in accounting service firms in Hanoi, Vietnam that have great effects on employees (or in this case study, accountants). There is not, statistically, significant difference in the level of nature of work of accountants in accounting service firms in Hanoi from these different genders and between the mentioned three groups of age. Based on the findings, some recommendations are given for accounting service firms to improve the nature of work of accountants.